2020
DOI: 10.1111/1365-2745.13339
|View full text |Cite
|
Sign up to set email alerts
|

Light availability and land‐use history drive biodiversity and functional changes in forest herb layer communities

Abstract: 1. A central challenge of today's ecological research is predicting how ecosystems will develop under future global change. Accurate predictions are complicated by (a) simultaneous effects of different drivers, such as climate change, nitrogen deposition and management changes; and (b) legacy effects from previous land use. 2. We tested whether herb layer biodiversity (i.e. richness, Shannon diversity and evenness) and functional (i.e. herb cover, specific leaf area [SLA] and plant height) responses to environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 66 publications
(84 reference statements)
11
53
1
1
Order By: Relevance
“…Community‐level SLA increased with decreasing light availability (and related increasing stand maturity), consistent with previous findings from temperate deciduous forests (Dahlgren et al 2006; Campetella et al 2011; Depauw et al 2019). This result is in contrast with findings from a study on temperate evergreen forest understories, where more conservative leaf traits values were revealed in older stands (Laughlin et al 2011).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Community‐level SLA increased with decreasing light availability (and related increasing stand maturity), consistent with previous findings from temperate deciduous forests (Dahlgren et al 2006; Campetella et al 2011; Depauw et al 2019). This result is in contrast with findings from a study on temperate evergreen forest understories, where more conservative leaf traits values were revealed in older stands (Laughlin et al 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Specific leaf area (SLA; light‐capturing surface area per unit dry biomass of a leaf; Pérez‐Harguindeguy et al 2013) is considered a key functional trait because it is a proxy for plant growth rate and resource economics, correlated with plant lifespan and a reliable surrogate for the ability to capture light (Poorter & Bongers 2006 and references therein; Auger & Shipley 2013; Depauw et al 2019). SLA is therefore an important trait informing shade tolerance strategies and may be very useful in characterizing forest understories with changing light availability conditions related to varying forest maturity (Lohbeck et al 2013; Blondeel et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Results of this study are in line with Depauw et al (2020). Studying herb layer structure and composition in semi-natural deciduous forests, they indicated that land-use history and light availability were the main, and more importantly, interacting environmental drivers of biodiversity and functional changes in forest understory.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were found in a study on biomass and leaf traits of twelve understory herbaceous plants -in most cases, generative plants had lower speci c leaf area than vegetative plants (Jagodziński et al 2016). Contrary to results of Depauw et al (2020), we found greater plant height decreases under more closed canopy in recent than in ancient forests, however, this could be a species-speci c reaction to changes in light conditions.…”
Section: Differences In Aboveground Biomass Allocation As a Survival supporting
confidence: 85%
See 1 more Smart Citation